Improving Russia's Policy on Foreign Direct Investment - Drebencov, Vladimir, 1959- 1959- (The World Bank, 1999)
May 2000 - Russia gets relatively little foreign direct investment and almost none of the newer, more efficient kind, involving state-of-the-art technology and world-class competitive production linked to dynamic global or regional markets. Why? And what should be done about it? Foreign direct investment brings host countries capital, productive facilities, and technology transfers as well as employment, new job skills, and management expertise. It is important to the Russian Federation, where incentives for competition are limited and incentives to becoming efficient are blunted by interregional barriers to trade, weak creditor rights, and administrative barriers to new entrants. Bergsman, Broadman, and Drebentsov argue that the old policy paradigm of foreign direct investment (established before World War II and prevalent in the 1950s and 1960s) still governs Russia. In this paradigm there are only two reasons for foreign direct investment: access to inputs for production and access to markets for outputs. Such kinds of foreign direct investment, although beneficial, are often based on generating exports that exploit cheap labor or natural resources or are aimed at penetrating protected local markets, not necessarily at world standards for price and quality. They contend that Russia should phase out high tariffs and nontariff protection for the domestic market, most tax preferences for foreign investors (which don't increase foreign direct investment but do reduce fiscal revenues), and many restrictions on foreign direct investment.